PENGARUH MEDIA MADING INTERAKTIF TERHADAP PEMAHAMAN NILAI-NILAI KEISLAMAN SISWA MATA PELAJARAN PAI KELAS IV DI SD NEGERI 141 PALEMBANG - Fina Agustin; Ahmad Syarifuddin; Agra Dwi Saputra; Aquami; Ines Tasya Jadidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of interactive wall magazine media on students’ understanding of Islamic values in the Islamic Education subject for fourth-grade students at SD Negeri 141 Palembang. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The sample consisted of class IVA as the experimental group and class IVB as the control group, with 47 students in total. Data were collected through observation, questionnaires, and documentation. The research instrument was a questionnaire measuring students’ understanding of Islamic values and had been tested for validity and reliability. The results showed that the average score of the experimental group was 74.00, while the control group was 61.04. The independent sample t-test obtained a significance value of 0.000 < 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. The coefficient of determination was 0.857, indicating a contribution of 85.7%. Therefore, interactive wall magazine media had a significant effect on students’ understanding of Islamic values in Islamic Education learning.